Measurement of halogenated dicarboxylic acids in the Arctic aerosols at polar sunrise - Narukawa, M.; Kawamura, K.; Hatsushika, H; Yamazaki, K; Li, S. M.; Bottenheim, J. W.; Anlauf, K. G. (JOURNAL OF ATMOSPHERIC CHEMISTRY, 2003)
Halogenated dicarboxylic acids, such as bromomalonic (Br-C-3), chlorosuccinic (Cl-C-4) and bromosuccinic (Br-C-4) acids, have been measured, for the first time, in the arctic aerosols during the polar sunrise experiment ALERT2000 ( February to May). They were detected in the light spring, but not in the dark winter. Concentration ranges of halogenated diacids in the spring were 0.11-0.68 ng m(-3) for Br-C-3 diacid, 0.04-0.10 ng m(-3) for Cl-C-4 diacid and 0.12-0.20 ng m(-3) for Br-C-4 diacid. Those of Br-C-3 diacid increased from late April to early May, whereas Cl-C-4 diacid decreased. In contrast, Br-C-4 diacid showed maximum concentrations in the middle of the experiment. A strong negative correlation (R = - 0.98) was obtained between Br-C-3 and Cl-C-4 diacids. Concentrations of methanesulfonic acid (MSA) also increased from late April to early May whereas those of Cl- ion decreased. A strong positive correlation was found between Cl-C-4 diacid and Cl- ion (R = 0.99) and between Br-C-3 diacid and MSA (R = 0.96). These results suggest that Br-C-3 diacid is primarily derived from marine biogenic source, whereas Cl-C-4 diacid is secondarily formed by heterogeneous reaction involving halogen chemistry on sea salt. Satellite images of sea ice concentrations and backward air mass trajectories suggest that the aerosols containing halogenated diacids were transported over the sampling sites from the Arctic Ocean covered with sea ice.